If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3x + -1 = 0 Reorder the terms: -1 + 2x + 3x = 0 Combine like terms: 2x + 3x = 5x -1 + 5x = 0 Solving -1 + 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 5x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 5x = 0 + 1 5x = 0 + 1 Combine like terms: 0 + 1 = 1 5x = 1 Divide each side by '5'. x = 0.2 Simplifying x = 0.2
| 7x-43=52 | | 3X+3/5=-2X-7/4 | | 4x^2-20x+10=0 | | -14-(-12)=x/2 | | 7-3(5t-10)=-67 | | x+3=12-1x | | 49=3x+9 | | -5x-10=2x+11 | | 52=3x+7 | | 17x+30=4(3x+6)+5x+6 | | 7y+3(y-9)=6(y+1)-2 | | 9(y-6)/2=-2y | | -29+7+(-18)+(-12)= | | -(25x+15y+80)= | | -5(3t-2)+4t=2t-7 | | 0/-22 | | -112/-21*-20 | | -4(2t-2)+3t=4t-6 | | xy+5x-10+2y= | | -2(4x-1)+9=-8x+11 | | .3x+5.35=9 | | 3x^2(2-x+4x^2)= | | 3x+3=3(x+8) | | -5w=10/7 | | -7w/9=-35 | | 5/6x+7/8-3/7x | | 6+2/3(12) | | -3/8w=-12 | | 4(x-1)+7=2x+2(1-x) | | -9y-9=8y+25 | | .3x+5.35=7 | | -7/8=w-2 |